Engineering Multi-Agent Systems Second International Workshop, EMAS 2014, Paris, France, May 5-6, 2014, Revised Selected Papers - Dalpiaz, Fabiano; Dix, Jürgen; van Riemsdijk, M. Birna; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the Second International Workshop on Engineering Multi-Agent Systems, EMAS 2014, held in Paris, France, in May 2014. The 22 full papers were carefully reviewed and selected from 41 submissions. The focus of the papers is on following topics: intelligent agents, multi-agent systems, software design engineering, model-driven software engineering, reasoning about belief and knowledge, cooperation and coordination, constraint and logic programming, software verification, design patterns.
Intelligent agents -- Multi-agent systems -- Software design engineering -- Model-driven software engineering -- Reasoning about belief and knowledge -- Cooperation and coordination -- Constraint and logic programming -- Software verification -- Design patterns.
Keywords: Artificial intelligence; Software engineering; Computer programming; Artificial Intelligence; Software Engineering; Programming Techniques